Rapid identification of Bordetella pertussis pertactin gene variants using LightCycler real-time polymerase chain reaction combined with melting curve analysis and gel electrophoresis. - Mäkinen, J (Centers for Disease Control and Prevention, 2001)
Recently, eight allelic variants of the pertactin gene (prn1-8) have been characterized in Bordetella pertussis strains isolated in Europe and the United States. It has been suggested that the divergence of the pertactin types of clinical isolates from those of the B. pertussis vaccine strains is a result of vaccine-driven evolution. Sequencing of the prn, which is relatively time-consuming, has so far been the only method for the differentiation of prn types. We have developed a rapid real-time polymerase chain reaction assay suitable for large-scale screening of the prn type of the circulating strains. This method correctly identified the prn type of all tested 41 clinical isolates and two Finnish vaccine strains. The method is simple and reliable and provides an alternative for sequencing in pertussis research.